Pharmacological Insights Into Safety and Efficacy Determinants for the Development of Adenosine Receptor Biased Agonists in the Treatment of Heart Failure - Rueda, Patricia; Merlin, Jon; Chimenti, Stefano; Feletou, Michel; Paysant, Jerome; White, Paul J.; Christopoulos, Arthur; Sexton, Patrick M.; Summers, Roger J.; Charman, William N.; May, Lauren T.; Langmead, Christopher J. (Frontiers in Pharmacology, 2021)
Adenosine A1 receptors (A1R) are a potential target for cardiac injury treatment due to their cardioprotective/antihypertrophic actions, but drug development has been hampered by on-target side effects such as bradycardia and altered renal haemodynamics. Biased agonism has emerged as an attractive mechanism for A1R-mediated cardioprotection that is haemodynamically safe. Here we investigate the pre-clinical pharmacology, efficacy and side-effect profile of the A1R agonist neladenoson, shown to be safe but ineffective in phase IIb trials for the treatment of heart failure. We compare this agent with the well-characterised, pan-adenosine receptor (AR) agonist NECA, capadenoson, and the A1R biased agonist VCP746, previously shown to be safe and cardioprotective in pre-clinical models of heart failure. We show that like VCP746, neladenoson is biased away from Ca2+ influx relative to NECA and the cAMP pathway at the A1R, a profile predictive of a lack of adenosine-like side effects. Additionally, neladenoson was also biased away from the MAPK pathway at the A1R. In contrast to VCP746, which displays more ‘adenosine-like’ signalling at the A2BR, neladenoson was a highly selective A1R agonist, with biased, weak agonism at the A2BR. Together these results show that unwanted haemodynamic effects of A1R agonists can be avoided by compounds biased away from Ca2+ influx relative to cAMP, relative to NECA. The failure of neladenoson to reach primary endpoints in clinical trials suggests that A1R-mediated cAMP inhibition may be a poor indicator of effectiveness in chronic heart failure. This study provides additional information that can aid future screening and/or design of improved AR agonists that are safe and efficacious in treating heart failure in patients.